Emergence of a new norovirus GII.6 variant in Japan, 2008-2009 - Wisoot Chan-It (2018)
Norovirus (NoV) is recognized as one of the most common causative agents of diarrhea disease in young children. A total of 187 fecal specimens collected from non-hospitalized children with acute gastroenteritis in Shizuoka, Japan during July 2008 to June 2009 were investigated for the presence of diarrhea viruses by a multiplex RT-PCR. Diarrhea viruses were overall detected in 158 of 187 (84.5%). Of the viruses detected, NoV was the most prevalent (55.6%). Most of the NoV sequences belonged to GII.4 (53.8%). NoV GII.6 emerged as the second most common strain (40.4%). The full-length capsid sequences of five representative Shizuoka GII.6 strains were compared with all 12 GII.6 strains available in GenBank database between 1990 and 2009. At least three distinct GII.6 subclusters (a-c) appeared in different parts of the world. Shizuoka GII.6 strains formed their own subcluster c, distinct from other complete GII.6 reference sequences. The Shizuoka strains had significant amino acid divergence, particularly in the P2 domain up to 10.9-17.5% and contained eight unique mutations in the P domains, compared with subcluster a and b viruses. The homology model showed that the eight mutations were predicted to be located at the surface-exposed P1 and P2 domains. The data suggest the emergence of a new NoV GII.6 variant in Shizuoka, with a high level of genetic variation. © 2012 Wiley Periodicals, Inc.